Social measures and disruptive innovations in entrepreneurship education to cope with COVID-19 - Hamburg, Ileana (Advances in Social Sciences Research Journal, 2021)
Entrepreneurship education (EE) can increase students’ entrepreneurial skills and intention but research results and experience show that entrepreneurship education still pursues conservative models, rather than forward-looking ones. The COVID-19 pandemic influenced all types and levels of education and training including entrepreneurship one. The article suggests several measures to be taken, also social ones, as a result of COVID-19 and how entrepreneurship education can be improved in order to support innovations and to be available for all. Advantages of an interdisciplinary perspective in EE and of mentoring as well as contribution of disruptive innovations at EE improvement are presented. An example of a European project in this context with contribution of the author and conclusions are given.